Private Sector Participation and Health System Performance in Sub-Saharan Africa - Yoong, J.; Burger, N.; Spreng, C.; Sood, N. (2012)
Background: The role of the private health sector in developing countries remains a much-debated and contentious issue. Critics argue that the high prices charged in the private sector limits the use of health care among the poorest, consequently reducing access and equity in the use of health care. Supporters argue that increased private sector participation might improve access and equity by bringing in much needed resources for health care and by allowing governments to increase focus on underserved populations. However, little empirical exists for or against either side of this debate. Methodology/Principal Findings: We examine the association between private sector participation and self-reported measures of utilization and equity in deliveries and treatment of childhood respiratory disease using regression analysis, across a sample of nationally-representative Demographic and Health Surveys from 34 SSA economies. We also examine the correlation between private sector participation and key background factors (socioeconomic development, business environment and governance) and use multivariate regression to control for potential confounders. Private sector participation is positively associated with greater overall access and reduced disparities between rich and poor as well as urban and rural populations. The positive association between private sector participation and improved health system performance is robust to controlling for confounders including per capita income and maternal education. Private sector participation is positively correlated with measures of socio-economic development and favorable business environment. Conclusions/Significance: Greater participation is associated with favorable intermediate outcomes in terms of access and equity. While these results do not establish a causal link between private sector participation and health system performance, they suggest that there is no deleterious link between private sector participation and health system performance in SSA.